2009
DOI: 10.1115/1.3049531
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermodynamical Admissibility of the Triphasic Theory of Charged Hydrated Tissues

Abstract: The triphasic theory on soft charged hydrated tissues (Lai, W. M., Hou, J. S., and Mow, V. C., 1991, "A Triphasic Theory for the Swelling and Deformation Behaviors of Articular Cartilage," ASME J. Biomech. Eng., 113, pp. 245-258) attributes the swelling propensity of articular cartilage to three different mechanisms: Donnan osmosis, excluded volume effect, and chemical expansion stress. The aim of this study is to evaluate the thermodynamic plausibility of the triphasic theory. The free energy of a sample of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…The osmo-poroviscoelastic formdulation used in this study was duly verified against thermodynamical consistency (Huyghe et al 2009). At the tissue level, the model was also validated, with parameter values that represented healthy tissues (Schroeder et al 2007).…”
Section: Discussionmentioning
confidence: 85%
“…The osmo-poroviscoelastic formdulation used in this study was duly verified against thermodynamical consistency (Huyghe et al 2009). At the tissue level, the model was also validated, with parameter values that represented healthy tissues (Schroeder et al 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Lai et al [143] introduced a triphasic mixture model, which includes three phases: an incompressible solid, an incompressible fluid, and a monovalent ionic phase. In the triphasic model, swelling behavior is explained by three mechanisms: Donnan osmosis, excluded volume effect, and chemical expansion [144]. Simon et al [145] introduced an alternative model by including the swelling effects in fluid equilibrium.…”
Section: Review Of Fibril Reinforced Computational Models Of Articmentioning
confidence: 99%
“…However, the inclusion of the chemical expansion term as proposed by Lai et al [143] may not be appropriate, as it conflicts with the second law of thermodynamics. Huyghe et al demonstrated that the chemical expansion stress part could produce free energy during closed loading cycles if the theory were true [144]. Nevertheless, osmotic swelling alone may not fully simulate the swelling behavior in cartilage [144].…”
Section: Review Of Fibril Reinforced Computational Models Of Articmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the swelling and the restriction against swelling determines the mechanical properties of the cartilage tissue 144,154 . Cartilage mechanical models have attempted to capture these effects of swelling with triphasic representations (solid, fluid, and ionic) 79,100,147 , fitting parameters to tissue-level consolidation experiments, or into computationally less expensive biphasic swelling models that assume ion flux is significantly faster than water flow 149 . To better capture the nature of the tissue, models with fiber-reinforcement were developed in the last decade 101,150,151 .…”
Section: Single Scale Approachesmentioning
confidence: 99%